Curvature comparison of Bézier curve, ball curve and trigonometric curve in preserving the positivity of real data - Afida, Ahmad (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2023)
Link to publisher's homepage at https://amci.unimap.edu.my/